Regulatory Functions of Nilaparvata lugens GSK-3 in Energy and Chitin Metabolism - Ding, Yan-Juan; Li, Guo-Yong; Xu, Cai-Di; Wu, Yan; Zhou, Zhong-Shi; Wang, Shi-Gui; Li, Can (Frontiers in Physiology, 2020)
Glucose metabolism is a biologically important metabolic process. Glycogen synthase kinase (GSK-3) is a key enzyme located in the middle of the sugar metabolism pathway that can regulate the energy metabolism process in the body through insulin signaling. This paper mainly explores the regulatory effect of glycogen synthase kinase on the metabolism of glycogen and trehalose in the brown planthopper (Nilaparvata lugens) by RNA interference. In this paper, microinjection of the target double-stranded GSK-3 (dsGSK-3) effectively inhibited the expression of target genes in N. lugens. GSK-3 gene silencing can effectively inhibit the expression of target genes (glycogen phosphorylase gene, glycogen synthase gene, trehalose-6-phosphate synthase 1 gene, and trehalose-6-phosphate synthase 2 gene) in N. lugens and trehalase activity, thereby reducing glycogen and glucose content, increasing trehalose content, and regulating insect trehalose balance. GSK-3 can regulate the genes chitin synthase gene and glucose-6-phosphate isomerase gene involved in the chitin biosynthetic pathway of N. lugens. GSK-3 gene silencing can inhibit the synthesis of chitin N. lugens, resulting in abnormal phenotypes and increased mortality. These results indicated that a low expression of GSK-3 in N. lugens can regulate the metabolism of glycogen and trehalose through the insulin signal pathway and energy metabolism pathway, and can regulate the biosynthesis of chitin, which affects molting and wing formation. The relevant research results will help us to more comprehensively explore the molecular mechanism of the regulation of energy and chitin metabolism of insect glycogen synthase kinases in species such as N. lugens.